ChemInform Abstract: One‐Pot Synthesis of (Z)‐β‐Sulfonyl Enoates from Ethyl Propiolate. Issue 4 (31st January 2013) - Downey, C. Wade; Craciun, Smaranda; Neferu, Ana M.; Vivelo, Christina A.; Mueller, Carly J.; Southall, Brian C.; Corsi, Stephanie; Etchill, Eric W.; Sault, Ryan
Abstract Addition of thiols to starting ester (I) in the presence of amine [cf.